Adverse clinical events in the hospital: characterization from the point of view of the health worker. - González-González, Abel; Domínguez Osorio, Isabel; Quero Palomino, Verónica; León Velasco, Magdalena; Polo Montres, Filomena; Lasso Ruales, Ximena Tatiana; Alonso, Lidia Martín (Medicina Clínica y Social, 2022)
Introduction: an adverse event is an incident that has caused harm to a patient and that may or may not be associated with a clinical error. A high percentage of health professionals are involved in this type of event annually. A large part of the professionals are unaware of the existence of the systems implemented in their work centers for a correct communication of adverse events. Objectives: to identify the characteristics of hospital professionals affected by an adverse event and to evaluate their knowledge of the notification systems. Methods: cross-sectional descriptive observational study. Demographic, labor and related variables with adverse events and notification systems were evaluated. Results: 207, 45.4% nurses and 54.6% doctors, participated, 39.24 ± 10.07 years and with an experience of 14.43 ± 9.9 years. 71.8% were affected by some adverse event. The first adverse event occurred at 6.45 ± 6.18 years. 42.1% knew of some notification system; but only 24.61% of these, affected by an adverse event, reported it. Physicians were more affected by an adverse event, moreover earlier (p
Keywords: Harm to patient, adverse events, patient safety, health personnel.